The Comparative Effects of Almond and Peanut on Adipose Tissue Profile and Blood Sugar Levels in Rats: A Review from an Islamic Perspective - prastina sari, Putri Agnia; Mukhtar, Diniwati; Ainur Rahmah, Nunung; Astiwara, Endy Muhammad (Junior Medical Journal, 2024)
Type 2 diabetes and cardiovascular disease are associated with high blood sugar and poor lipid profiles. Almonds and peanuts have the potential to reduce these risks. This study aims to evaluate the effects of these two nuts on blood sugar levels and lipid profiles, within the Islamic perspective of halal and thayyib foods. An experimental study was conducted with 4 groups: standard feed (K1), high-fat feed (K2), almond feed (K3), and peanut feed (K4) over 4 weeks. Blood sugar measurements were taken using the GOD-PAP method, and histopathological analysis of adipose tissue was performed using Hematoxylin-Eosin (HE) staining. The results showed that both almonds and peanuts significantly (P<0.05) increased blood sugar levels. When compared to the high-fat feed group, the nut groups were more effective in inhibiting this increase. However, changes in blood sugar levels and lipid profiles were not statistically significant (P>0.05). From the study results, it can be concluded that there are differences in blood sugar and lipid profiles after the consumption of almonds and peanuts, although not significant. The consumption of halal and thayyib foods is recommended in Islam.